Disentangling the “net” from the “offset”: learning for net-zero climate policy from an analysis of “no-net-loss” in biodiversity - McLaren, Duncan P.; Carver, Louise (Frontiers in Climate, 2023)
Net-zero has proved a rapid and powerful convening concept for climate policy. Rather than treating it as a novel development from the perspective of climate policy, we examine net-zero in the context of the longer history and experience of the “no-net-loss” framing from biodiversity policy. Drawing on material from scholarly, policy and activist literature and cultural political economy theory, we interpret the turn to “net” policies and practices as part of the political economy of neoliberalism, in which the quantification and commodification of the environment, and in particular—trading through an offset market, enable continued ideological dominance of economic freedoms. This analysis highlights the ways in which the adoption of a “net” framing reconstructs the goals, processes and mechanisms involved. It is the neoliberal commitment to markets that drives the adoption of net framings for the very purpose of validating offsetting markets. Understanding the making of “net” measures in this way highlights the potential to disentangle the “net” from the “offset”, and we discuss the various obfuscations and perversities this entanglement affords. We argue that the delivery of net outcomes might be separated from the mechanism of offsetting, and the marketization of compensation it is typically presumed to involve, but may yet remain entangled in neoliberal political ideology. In conclusion we suggest some conditions for more effective, fair and sustainable delivery of “net-zero” climate policy.